Sistem Informasi Donasi Digital Amal Now Berbasis Laravel: Studi Perancangan dan Implementasi - Dhika Neissa Asanti; Abim Febri Hananto; Nabilah Maimunnah; Wildan Setiawan (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The advancement of information technology has driven transformation in various aspects of life, including in the practice of digital donations. However, there are still many challenges related to ease of access, transparency, and accountability in the online donation process. This research aims to design and implement a web-based digital donation information system called AmalNow, which serves as a platform connecting donors, administrators, and donation coordinators. The research method used is a software engineering approach with the Waterfall model, which includes stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the Laravel framework and MySQL database, with integration of the Midtrans payment gateway. The research findings indicate that AmalNow is capable of meeting functional needs such as campaign management, donation transactions, real-time reporting, as well as supporting non-functional needs such as security, efficiency, and ease of use. With the support of a structured system architecture and an intuitive user interface, this application is expected to be a reliable and effective digital donation solution in enhancing social participation in the community.